2011
DOI: 10.1007/s10529-011-0575-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional identification of hyoscyamine 6β-hydroxylase from Anisodus acutangulus and overproduction of scopolamine in genetically-engineered Escherichia coli

Abstract: Hyoscyamine 6β-hydroxylase (H6H; EC 1.14.11.11) converts hyoscyamine to scopolamine in the last step of scopolamine biosynthetic pathway. The gene encoding H6H in Anisodus acutangulus was cloned and expressed in Escherichia coli and the recombinant proteins fused with His-tag or GST-tag at its N-terminal were purified and then confirmed by Western bolt analysis. The biofunctional assay revealed that the His-AaH6H and GST-AaH6H converted hyoscyamine (40 mg/l) to scopolamine at 32 and 31 mg/l, respectively. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Additionally, specific hydroxylase and epoxidase activity: 2.60 ± 0.19 nKat mg −1 and 0.24 ± 0.02 nKat mg −1 for these two compounds were observed, respectively. The H6H from Anisodus acutangulus was cloned and expressed in E. coli fused with either a His- or GST-tag at the N -terminus [109]. A bifunctional assay revealed that both recombinant enzymes converted up to 80% of fed hyoscyamine to scopolamine, however, reaction kinetics were not analysed.…”
Section: Biotechnological Approaches Of Scopolamine Production Andmentioning
confidence: 99%
“…Additionally, specific hydroxylase and epoxidase activity: 2.60 ± 0.19 nKat mg −1 and 0.24 ± 0.02 nKat mg −1 for these two compounds were observed, respectively. The H6H from Anisodus acutangulus was cloned and expressed in E. coli fused with either a His- or GST-tag at the N -terminus [109]. A bifunctional assay revealed that both recombinant enzymes converted up to 80% of fed hyoscyamine to scopolamine, however, reaction kinetics were not analysed.…”
Section: Biotechnological Approaches Of Scopolamine Production Andmentioning
confidence: 99%
“…However, our previous results found that AaH6H did not have the activity to convert scopolamine into anisodine. 26 In fact anisodine and scopolamine have similar chemical structures, but anisodine possesses a hydroxyl-group on the a-carbon atom of the tropic acid moiety. 27 The biosynthetic pathway of anisodine is not yet clear, but it can be deduced that it may be synthesized from scopolamine by an unknown hydroxylase in view of the chemical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Hyoscyamine 6 β -hydroxylase (H6H) catalyzes hyoscyamine to produce anisodamine through 6 β -hydroxylation, and subsequently oxidizes anisodamine to generate scopolamine ( Hashimoto and Yamada, 1986 ) The H6H genes have been identified from H. niger ( Hashimoto and Yamada, 1986 ), A. belladonna ( Li et al, 2012 ), A. acutangulus ( Kai et al, 2011a ), and S. luridus ( Lan et al, 2018 ). Of these H6H enzymes, the H. niger one (HnH6H) showed the highest efficiency in converting hyoscyamine to scopolamine, and HnH6H is the best choice in engineering scopolamine production.…”
Section: Engineering Medicinal Tropane Alkaloid Production In Hairy R...mentioning
confidence: 99%